2022
DOI: 10.1007/s40121-022-00717-6
|View full text |Cite
|
Sign up to set email alerts
|

Hospitalization Burden Related to Herpes Zoster Infection in Spain (2016–2019)

Abstract: Introduction: Herpes zoster (HZ) and its complications still represent a significant burden for patients and health care systems. In Spain, vaccination is progressively being introduced and recommended for patients between 65 and 80 years old and patients [ 18 years of age suffering from certain immunosuppression conditions. The aim of this study is to estimate the number of hospital admissions related to HZ from 2016 to 2019 in Spain. Methods: Data were collected from the Minimum Basic DataSet (MBDS) and codi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1
5

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 32 publications
0
7
1
5
Order By: Relevance
“…Despite a decrease in the hospitalization rate, during the years analyzed, the mortality rate increased. This discrepancy between hospitalization rate and mortality rate does not correspond to the epidemiological reality or to the trend reported by previous studies 11 , 17 , 26 but to factors related to the worst years of the pandemic. The fear of contagion from COVID-19 together with the confinement measures may be some of the causes that delayed visits to emergency rooms.…”
Section: Discussioncontrasting
confidence: 90%
See 3 more Smart Citations
“…Despite a decrease in the hospitalization rate, during the years analyzed, the mortality rate increased. This discrepancy between hospitalization rate and mortality rate does not correspond to the epidemiological reality or to the trend reported by previous studies 11 , 17 , 26 but to factors related to the worst years of the pandemic. The fear of contagion from COVID-19 together with the confinement measures may be some of the causes that delayed visits to emergency rooms.…”
Section: Discussioncontrasting
confidence: 90%
“…This confirms immunosenescence as the main risk factor in the population. 17 , 25 Regarding sex, the number of hospitalizations was higher among women than among men. This difference may not be real and may be because women request more consultations from the health system.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…[7] The occurrence of HZ is significantly associated with immunocompromise, hypertension, and diabetes, [7,8] posing huge nursing and economic burden. [9,10] Clinical practice guidelines recommend antiviral therapies to hasten healing time (acyclovir, valacyclovir, famciclovir, and brivudine), [11][12][13][14] and pain management treatments such as paracetamol/acetaminophen, opioid analgesics, tricyclic antidepressants and anticonvulsants for significant pain, but the therapeutic effects are far from satisfying and there is limited evidence in reducing the incidence of PHN. [15] One study using the Treatment Satisfaction Questionnaire for Medication (TSQM, Version II) to assess patient satisfaction with HZ treatment showed that patient satisfaction was highest in the "side effects" area of TSQM and lowest in the "effectiveness" area.…”
Section: Introductionmentioning
confidence: 99%